2017
DOI: 10.1111/exd.13444
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the epidermal expression of glucocorticoid receptor‐beta as potential predictive marker of bullous pemphigoid outcome

Abstract: Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering disease in Western countries. Although topical and/or systemic glucocorticoids treatment efficacy is widely recognized, up to 30% of patients with BP may undergo a relapse during the first year of treatment. We investigated the protein expression of the total glucocorticoid receptor and GRβ isoform in the skin biopsy specimens from patients with BP and wondered whether such investigation at baseline provided a tool to predict disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…This is also in setting with the low prevalence of anti-type VII collagen antibodies in other autoimmune and autoinflammatory diseases, such as inflammatory bowel disease (16%) and pemphigus (9.5%), but also in healthy subjects ( 38 ). Furthermore, the low titer of anti-type VII collagen AAb in comparison with the high titer of anti-BP180 antibodies in our two patients with mucous membrane involvement, like in these other diseases, rather points out the production of anti-type VII collagen antibodies in BP as an epiphenomenon, as previously suggested ( 31 ). A possible diversification of the AAb response in BP could be related at least in part to disease severity, as BP patients with mucosal involvement had higher total and skin BPDAI scores, especially the blisters/erosions activity score, as compared with the BPDAI score from patients with a typical form of BP ( 41 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is also in setting with the low prevalence of anti-type VII collagen antibodies in other autoimmune and autoinflammatory diseases, such as inflammatory bowel disease (16%) and pemphigus (9.5%), but also in healthy subjects ( 38 ). Furthermore, the low titer of anti-type VII collagen AAb in comparison with the high titer of anti-BP180 antibodies in our two patients with mucous membrane involvement, like in these other diseases, rather points out the production of anti-type VII collagen antibodies in BP as an epiphenomenon, as previously suggested ( 31 ). A possible diversification of the AAb response in BP could be related at least in part to disease severity, as BP patients with mucosal involvement had higher total and skin BPDAI scores, especially the blisters/erosions activity score, as compared with the BPDAI score from patients with a typical form of BP ( 41 ).…”
Section: Discussionsupporting
confidence: 75%
“…Actually, high serum level of anti-BP180 NC16A AAb was correlated with disease activity at time of diagnosis and was shown as an independent risk factor for BP relapse after cessation of therapy ( 14 , 15 , 25 27 ). In addition, approximately 30% of the BP patients relapse during the first year of treatment ( 16 , 28 31 ). For those latter BP patients, it was shown that the variations of serum IgG AAb directed toward the BP180 NC16A domain after 2 months of therapy may be useful to predict BP outcome ( 16 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increased expression of the glucocorticoid receptor-beta in skin epithelial cells was suggested to be predictive of reduced treatment efficacy and increased risk of BP relapse (225). The presence of extensive disease (more than ten new blisters daily) at baseline and of neurological conditions associated with BP (e.g., dementia) may also play a role in the prediction of BP outcome (219).…”
Section: Predictive Biomarkers For Disease Progressionmentioning
confidence: 99%
“…23,43 However, the refractory nature of some patients to corticosteroids merits further study. 44,45…”
Section: Bullous Pemphigoidmentioning
confidence: 99%